Trace cadmium determination in lake water matrix by flame atomic absorption spectrometry after manganese ferrite magnetic nanoparticles-based dispersive solid phase extraction - Karaman, Devrim Nur; Serbest, Hakan; Kilinc, Yagmur; Demirel, Rabia; Bakirdere, Sezgin (WILEY, 2023)
In this study, manganese ferrite magnetic nanoparticles-based dispersive solid phase extraction (MF-MNP-DSPE) was developed for cadmium determination at trace level by flame atomic absorption spectrometry (FAAS). Manganese ferrite-based magnetic nanoparticles were synthesized to be used as solid phase extraction sorbent. All the analytical conditions were optimized by univariate optimization approach to achieve high enrichment factors. Under the optimum conditions, limit of detection (LOD) and quantification (LOQ) values of the developed method were recorded as 1.3 and 4.3 & mu;g L-1, respectively. Approximately 135-fold improvement in the detection power by the MF-MNP-DSPE-FAAS system was recorded over the traditional FAAS system based on LOD comparison. Recovery experiments were performed to test the applicability/accuracy of the developed method with lake water spiked at different concentrations. Percent recovery values were obtained between 87% and 112% by employing the matrix matching calibration strategy and this showed that the developed method is applicable for the determination of cadmium in lake water samples with high accuracy and precision.
Keywords: cadmium; dispersive solid phase extraction; flame atomic absorption spectrophotometry; manganese ferrite magnetic nanoparticles; CLOUD POINT EXTRACTION; ONLINE PRECONCENTRATION; AQUEOUS-SOLUTION; METAL-IONS; LEAD; MICROEXTRACTION; ADSORPTION; SEPARATION; ADSORBENT; CHROMIUM; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources